Effectiveness and safety of pembrolizumab, nivolumab, and atezolizumab as adjuvant therapy for high-risk muscle-invasive urothelial carcinoma: an indirect comparison - Chen, Wei; Yoshida, Soichiro; Miura, Noriyoshi; Fukuda, Shohei; Fukushima, Hiroshi; Waseda, Yuma; Tanaka, Hajime; Fujii, Yasuhisa (Frontiers in Oncology, 2025)
BackgroundThe effectiveness of immune checkpoint inhibitors (ICIs) as adjuvant therapy for muscle-invasive urothelial carcinoma (MIUC) with high recurrence risk has been demonstrated. With no direct efficacy comparisons available, we aimed to indirectly compare the efficacy and safety of pembrolizumab, nivolumab, and atezolizumab as adjuvant treatments for high-risk MIUC based on individual patient data (IPD) from clinical trials.MethodsIPD was reconstructed using the Shiny method from Kaplan–Meier curves of eligible randomized controlled trials. We compared disease-free survival (DFS), overall survival (OS), PD-L1 positive DFS between treatments, and assessed treatment-related adverse events (TRAE).ResultsFour studies including 2,220 high-risk MIUC patients showed no statistically significant difference between the three agents in terms of DFS (pembrolizumab vs. nivolumab: HR 0.97, 95% CI 0.79–1.18; pembrolizumab vs. atezolizumab: HR 0.85, 95% CI 0.70–1.04; nivolumab vs. atezolizumab: HR 0.90, 95% CI 0.74–1.10). All three agents showed comparable DFS outcomes in PD-L1 positive patients (pembrolizumab vs. nivolumab: HR 1.16, 95% CI 0.83–1.60; pembrolizumab vs. atezolizumab: HR 0.85, 95% CI 0.84–1.14; nivolumab vs. atezolizumab: HR 0.79, 95% CI 0.57–1.09), with similar DFS rates 24- and 36-months post-treatment (pembrolizumab: 53.3% and 46.8%; nivolumab: 48.5% and 44.8%; Atezolizumab: 45.0% and 40.7%). OS data showed no significant differences between pembrolizumab and nivolumab (HR 1.16, 95% CI: 0.90–1.49), pembrolizumab and atezolizumab (HR 1.02, 95% CI: 0.81-1.30), and nivolumab and atezolizumab (HR 0.87, 95% CI: 0.69–1.09). TRAE incidence varied but remained manageable (any grade: 26.4% pembrolizumab, 78.6% nivolumab, 54% atezolizumab; grade ≥3: 21.8% pembrolizumab, 18.2% nivolumab, 16.0% atezolizumab).ConclusionsAll three agents showed similar efficacy with manageable safety profiles, positioning them as promising adjuvant therapies for MIUC. These results provide an evidence-based framework for clinical decision-making despite the lack of direct comparative data.